2018
DOI: 10.1007/s42452-018-0137-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between electrocoagulation and solvent extraction method in the process of the dechlorophyllation of alcoholic extracts from Moroccan medicinal plants Petroselinum crispum, Thymus satureioides and microalgae Spirulina platensis

Abstract: The air-dried aerial leaves of Petroselinum crispum, Thymus satureioides and dried Spirulina platensis powder were separately extracted using a Soxhlet apparatus. The dark green solution obtained was subject to the dechlorophyllation by two techniques, the electrocoagulation and solvent extraction. The obtained absorbances, were particularly much lower for electrocoagulation process. This result showed that this technique can remove easily plant pigments in the extracts, without affecting the chemical composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Here, we showed that the extract contains a high content of total phenolics and flavonoids and exhibits a strong antioxidant potential using both DPPH and ABTS assays. Similar observations were reported showing that T. satureioides extracts were the richest in total phenolics (up to 70.2 mg GAE/g) and flavonoids (up to 52.7 mg QuE/g) compared to the other extracts from Petroselinum crispum and the microalgae Spirulina platensis [26]. Elsewhere, the aqueous extract of T. satureioides was also shown to elicit ferric-reducing antioxidant power (FRAP) at up to 7.03 ± 0.29 mmol trolox/g [27].…”
Section: Discussionsupporting
confidence: 89%
“…Here, we showed that the extract contains a high content of total phenolics and flavonoids and exhibits a strong antioxidant potential using both DPPH and ABTS assays. Similar observations were reported showing that T. satureioides extracts were the richest in total phenolics (up to 70.2 mg GAE/g) and flavonoids (up to 52.7 mg QuE/g) compared to the other extracts from Petroselinum crispum and the microalgae Spirulina platensis [26]. Elsewhere, the aqueous extract of T. satureioides was also shown to elicit ferric-reducing antioxidant power (FRAP) at up to 7.03 ± 0.29 mmol trolox/g [27].…”
Section: Discussionsupporting
confidence: 89%
“…5). This finding is in agreement with the results of works [31][32][33][34] on the extracts who indicate that the solvent mixture water/alcohol would better extract phenolic compounds than alcohol alone. The use of ethanol/water mixture (67/33 v/v) in this study could justify thus a high solubility of the phenolic compounds.…”
Section: Total Tannins Content (Ttc)supporting
confidence: 93%
“…Interestingly, Kouar et al [ 38 ] have determined the phytochemical profile of alcoholic extract of T. satureioides leaves, using the electrocoagulation and solvent extraction assays, and detected the presence of saponins, sterols, triterpene, tannins, and flavone aglycones. The quantitative analysis showed that T. satureioides alcoholic extract contains high levels of total polyphenols (70.2 ± 0.4 mg of gallic acid equivalents/g extract) and total flavonoids (52.7 ± 0.01 mg of quercetin equivalents/g extract).…”
Section: Resultsmentioning
confidence: 99%